Psychological Loneliness and Its Relationship to Social Support Among Female Detainees Released from the Occupation Prisons in the Governorates of the West Bank - Aweis, Amane Mohammed (Journal of Humanities & Social Sciences, 2020)
This study aimed to identify the level psychological loneliness and social support among female detainees released from the occupation prisons in the governorates of the West Bank, identify the statistically significant differences in the degrees of the scale of psychological loneliness and social support and its dimensions in the freed detainees from the occupation prisons in the governorates of the West Bank according to the (age, marital status, educational level, duration of detention) variables, and to know the nature of the relationship between the psychological loneliness and social support of the freed detainees from the occupation prisons in the governorates of the West Bank. The study followed the descriptive analytical method, and its population consisted of all female detainees released from the occupation prisons in the governorates of the West Bank, with a random sample of (40) female detainees were taken. The study used a measure of psychological loneliness and social support. The results showed the following: A) The level of psychological loneliness among female detainees released from the occupation prisons in the governorates of the West Bank reached 71.8% and level of social support reached 58.4%. B) There is statistically significant relationship between the psychological loneliness and social support of female detainees released from the occupation prisons in the governorates of the West Bank. C) There are no statistically significant differences in the degrees of the psychological loneliness scale of female detainees released from the occupation prisons in the governorates of the West Bank due to age, educational level, marital status, and length of detention variables. D) There are no statistically significant differences in the scores for the scale of social support among female detainees released from the occupation prisons in the governorates of the West Bank due to age, educational level, and marital status variable. E) There are statistically significant differences in the scores for the scale of social support among female detainees released from the occupation prisons in the West Bank governorates due to the variable period of detention. In light of the results, the study recommended the following: 1) The necessity of holding sessions, conferences and seminars to improve the psychological state of the freed female detainees after the prison period to identify the most important psychological problems that were reflected on them. 2) The necessity of designing educational and psychosocial support programs for freed women detainees to solve psychological and social problems.